THE EFFECT OF ORGANIZATIONAL SUPPORT AND WORK MOTIVATION ON PERFORMANCE EMPLOYEES (PT Huadi Nickel Alloy Indonesia Bantaeng Regency) - Amirullah (Scientia Integritas Utama, 2022)
The purpose of this study was to examine the relationship between organizational support and work motivation on employee performance. The sampling technique used a survey method, which took all employees, population and research samples using questionnaires to 95 employees of PT Huadi Nickel Alloy Indonesia, Bantaeng Regency. The analytical method used is inferential analysis with a path analysis approach. Based on the results of the research and discussion that has been carried out, the conclusions that can be drawn are (1) The results of hypothesis testing indicate that the organizational support variable is proven to have a positive and significant influence on employee performance. (2) The results of hypothesis testing show that the organizational support variable is proven to have a positive and significant effect on work motivation. (3) The results of hypothesis testing show that the work motivation variable is proven to have a positive and significant effect on employee performance. (4) The test results show that work motivation is proven to mediate the effect of organizational support on employee performance at PT Huadi Nickel Alloy Indonesia, Bantaeng Regency